Enhancing rapeseed (Brassica napus L.) productivity through frontline demonstrations approach in Ferozepur district of Punjab - Jagdeep Kaur; Gurjant Singh Aulakh (Journal of Oilseed Brassica, 2026)
Frontline demonstrations were conducted in district Ferozepur on canola variety of gobhi sarson during the year 2018-19 with the objective to enhance production and productivity of canola gobhi srason with economic benefits at farmer’sfield through improved production technologies. The results of the study revealed that GSC-7 canola gobhi sarsonvariety gave average yield of 22.5 q/ha as compared to 17.8 q/ha of local variety with an increase in yield of 26.4% overlocal variety. Moreover, the cultivation of canola gobhi sarson (GSC-7) under frontline demonstrations yielded additionalgain of Rs. 19480/ha over farmer’s practice.